Parametric optimizationof friction stir spot welded aluminium AA6063 alloy joints. (2021) - Raj kumar, P.; Nandhakumar, S.; Seenivasan, S.; Chandraprakash, R.
Abstract: Friction stir spot welding is a solid-state welding process where the joints are formed due to plastic deformation. This technique is economically sound and more efficient when compared to that of other spot welding. In this research Taguchi approach has been applied to determine the most influential control factors which will yield better tensile strength of the joints of friction stir spot welded AA6063 aluminium alloy. In order to evaluate the effect of process parameters such as tool rotational speed, tool profile and axial force on tensile strength of friction stir spot welded AA6063 aluminium alloy. Taguchi method was used to obtain significant and optimum levels of process parameters. Mathematical model has been developed using ANOVA based Taguchi method, which were further used to predict the ultimate tensile strength of friction stir spot welded joints of 6063 aluminium alloys. Rotational speed, tool profile and axial force were found significant parameters in deciding the ultimate tensile strength of the joint. The optimum value of ultimate tensile strength of welded joints obtained from experiment. The results obtained has been analyzed and optimized by analysis of variance-based Taguchi method.